Endoscopic polypectomy performed in clinic for chronic rhinosinusitis with nasal polyps: study protocol for the EPIC multicentre randomised controlled trial. Issue 12 (2nd December 2020) - Kilty, Shaun; Thavorn, Kednapa; Janjua, Arif; Lee, John; MacDonald, Kristian; Meen, Eric; Micomonaco, Damian; Rotenberg, Brian; Sowerby, Leigh J; Tewfik, Marc; Adams, Susan; Frenette, Hubert; et al.
Abstract : Introduction: Chronic rhinosinusitis (CRS) is common, with a Canadian prevalence of 5%, and associated with significant morbidity. Understandably, CRS impairs workplace productivity but that productivity substantially increases following surgical treatment. CRS with nasal polyps (CRSwNP), the most common type of CRS, is usually treated with a combination of medications and endoscopic sinus surgery (ESS). Historically, surgical treatment has only been performed in the operating room at a cost of about C3500. However, recent studies have shown that a de-escalated procedure, endoscopic polypectomy performed in clinic (EPIC), can provide an improvement in patient symptoms to levels equal to those for ESS. Moreover, EPIC has additional proposed advantages including shorter recovery time, significantly lower cost to the healthcare system and shorter wait time for the patient. There is currently insufficient evidence to draw conclusions about the superiority of polypectomy or ESS for the management of CRSwNP. Methods and analysis: We designed a multicentre, open-label, randomised controlled trial to evaluate whether EPIC was non-inferior to the current clinical standard, ESS for the treatment of CRSwNP. The primary outcome is the Sinonasal Outcome Test-22 score measured at baseline and at 3 months after surgery. Other outcomes include peak nasal inspiratory flow, quality of life measured by the EuroQoL 5 Dimensions 5 Levels questionnaire and work impairment using the Work Productivity and Activity Impairment Questionnaire. We aim to recruit 140 patients from sites across Canada. Participants will be randomly assigned to EPIC or ESS and followed up for 3 months in clinic after the procedure. Additionally, participants will enter a 5-year long-term follow-up period. Ethics and dissemination: This study was approved by the Ottawa Health Sciences Network Research Ethics Board for all sites in Ontario, Canada (study number CTO0801). Sites located outside of Ontario obtained approval from their local/institutional research ethics board. Trial registration number: NCT02975310 .